TikTok Application-Based Learning Videos on Climate Change Materials at the Junior High School Level - Darmilus Darmilus; Hartono Hartono; Syarifuddin Syarifuddin (Edumaspul: Jurnal Pendidikan, 2024)
Climate change has become one of the most urgent global issues that needs to be addressed immediately. The United Nations (UN) invites all countries to become catalysts in accelerating public education, especially the younger generation, so they have the knowledge and awareness to protect the environment. Nowadays, we live in a world where knowledge and information are very easy to obtain thanks to the help of the internet. TikTok is an example of an information dissemination platform that has proven effective in educating the public, especially Generation Z, whose life is closely linked to technology. This research aims to analyse the need to develop learning media in the form of TikTok for climate change material at the junior high school level. Using quantitative descriptive methods, researchers will collect data using interview techniques and distributing questionnaires. The data obtained is then presented in descriptive form. Overall, the research results show that students do not understand climate change in depth and want to learn more about it through TikTok videos.